Sosialisasi Dan Praktik Pengisian Buku Administrasi Bank Sampah “Sami Berkah” Kecamatan Tembalang Kota Semarang - Aniqotunnafiah; Endang Dwi Wahyuningsih; Kasidi; Nikmatul Hasanah; Ika Sabrina Luthfi (Jurnal Pengabdian kepada Masyarakat STIE AKA Semarang, 2025)
Abstract: Waste has become a serious threat to environmental sustainability and a contributing factor to global warming. Waste banks are a strategic solution to reduce the impact of waste generation by implementing the 3R principle (Reduce, Reuse, Recycle). This community service activity aims to improve the administrative and financial management capabilities of the "Sami Berkah" Waste Bank, located in Desa Meteseh, Kecamatan Tembalang, Kota Semarang. The implementation method included lectures, mentoring, and hands-on practice in filling out administrative books, including the Member Registration Book, Waste Bank Savings Book, Member List, Financial Ledger, Member Deposit Summary Book, and Attendance List. The activity results showed that Waste Bank administrators and members were able to follow and carry out the administrative book filling process effectively through simulations of new member registration and waste deposits. Proper bookkeeping administration has been proven to optimize waste management and increase operational effectiveness. However, there are still limitations in terms of digital information access for customers and the preparation of comprehensive financial reports. This activity makes a significant contribution to increasing transparency and accountability in Waste Bank management as a business unit that manages waste for the community. Keywords: Waste Bank, Financial Administration, Transparency, Accountability, Waste Management